Razvoj i aktualne tendencije pedagogije i školstva na području nekadašnje Jugoslavije - Protner, Edvard (2020)
Development and Curent Trends in Education on the Territory of the Former Yugoslavia. It has been almost ten years since the Department of Pedagogy of the Faculty of Arts, University of Maribor, initiated cooperation through projects in the field of comparative pedagogy and the history of pedagogical ideas and education in the region. A group of academics from the countries of the former Yugoslavia was formed (unfortunately we have not succeeded in including Kosovo), which has carried out several joint projects over the years. This monograph provides analyses of three thematic sections: 1. The development of teacher education in the former Yugoslavia; 2. School education and pedagogy during socialism in the former Yugoslavia; 3. Pedagogy in the former Yugoslavia between the past and the present. These texts have been presented at symposiums and published in English and Slovenian; their translation into Croatian will ensure that they are widely accessible to the professional public and to students in pedagogical study programs at universities in the countries of the former Yugoslavia.
Keywords: teacher education; socialism; school system; study; Jugoslavia; history of education